2020
DOI: 10.1093/mtp/miaa017
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Music Therapy: Developing New Approaches to Service Delivery

Abstract: As the global Coronavirus disease (COVID-19) pandemic transforms our society, music therapists must adapt service delivery models that ensure client safety. Given the prevalence of COVID-19 in our communities and lack of personal protective equipment in many settings, music therapists are faced with the need to shift delivery models in order to provide safe and relevant services. Telehealth is one solution to these current service delivery challenges. Music therapists possess a depth of practice-based knowledg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(68 citation statements)
references
References 7 publications
1
63
0
4
Order By: Relevance
“…Ten articles were included in this scoping review, eight of them identified through database search (published and unpublished sources) [ 2 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ] and two identified through a manual search of websites of MT associations [ 23 , 24 ]. The basic characteristics are in Table 1 and all data-charting tables and a data summary table are in Supplementary S3 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ten articles were included in this scoping review, eight of them identified through database search (published and unpublished sources) [ 2 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ] and two identified through a manual search of websites of MT associations [ 23 , 24 ]. The basic characteristics are in Table 1 and all data-charting tables and a data summary table are in Supplementary S3 .…”
Section: Resultsmentioning
confidence: 99%
“…[23] Preparing the client: You [client] need to consider the room you're in quite carefully-quiet, so not much background noise, and that's unlikely to be disturbed for the duration of your session; background, good light. [17,24] Adaptation concerning the space:…”
Section: Adaptation Of the Goalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, some practitioners have been honing the art of teletherapy. Knott and Block (2020), for example, offer a model for VMT that describes how to develop VMT that carefully considers the clinical goals, and ensures that the online format is as accessible, appropriate (taking into consideration the patient's abilities), and effective as possible to meet the patient's needs. Further, Molyneux et al (2020) describe how continuing to deliver sessions virtually provided support, continuity, and an ongoing connection for people living with dementia and their companions who were isolated in their own homes due to the national lockdown in the United Kingdom.…”
Section: Online Music Therapy and The Challenge Of Administering Mt During The Covid-19 Pandemicmentioning
confidence: 99%
“…MT interventions can also save time, weigh less on staff and equipment resources in pediatric care ( Millett & Gooding, 2018 ), and reduce procedural time ( Chlan, Heiderscheit, Skaar, & Neidecker, 2018 ). During the Covid outbreak, literature explored recommendations to expand tools and employ communication technologies in order to stay in contact with patients ( Clerici et al, 2020 ; Knott & Block, 2020 ; Giordano, Scarlata et al, 2020 ; Marianne Rizkallah, 2020), and several professional MT organizations paid particular attention to remote intervention modalities ( AMTA, 2020; BAMT, 2020; AIM, 2020). However, in our context, support with MT was completely suspended for 3 months.…”
Section: Introductionmentioning
confidence: 99%